PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN GUDANG PADA PT PULAU BARU JAYA - Sri Mulyani; Ni Nyoman Suarniki; Muhammad Yusuf Ilmi (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
This study aims to determine the effect of occupational safety and health programs on the work productivity of PT Pulau Baru Jaya employees. The population in this study is the total number of employees in the Warehouse section at PT Pulau Baru Jaya, which totals 68 employees. According to Arikunto (2006: 120)